Pengaruh Diferensiasi Produk dan Inovasi Produk terhadap Keunggulan Bersaing Motor Honda Beat Street di Kota Medan (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the effect of product differentiation and product innovation on the competitive advantage of the Honda Beat Street motorcycle in Medan City. The research employed a quantitative method with an associative approach, involving 97 respondents who are users of Honda Beat Street. Data were collected through questionnaires and analyzed using validity tests, reliability tests, multiple linear regression, t-tests, and F-tests. The results show that product differentiation has a positive and significant effect on competitive advantage, with durability emerging as the most dominant indicator. Product innovation also has a positive and significant effect, with product design being the highest-rated indicator. Simultaneously, both differentiation and innovation significantly influence competitive advantage, as indicated by an Adjusted R Square value of 59.1%. These findings indicate that Honda’s differentiation and innovation strategies play an important role in strengthening the competitive position of Honda Beat Street in the Medan market. The study suggests that the company should enhance stylistic elements, enrich product variations, and consistently improve innovation to maintain relevance and competitiveness.